Modulation of the pressor response elicited by carbachol and electrical stimulation of the amygdala by muscarinic antagonists in conscious rats - (:unkn) unknown (STOCKTON PRESS, 1997)
1 The nature of the muscarinic receptor involved in mediating cardiovascular changes caused by unilateral microinjection of carbachol (5 nmol) into, and electrical stimulation (200-300 mu A) of, the amygdaloid complex was investigated in conscious, unrestrained female Sprague-Dawley rats. 2 Unilateral microinjection of carbachol (5 nmol; n=6) and electrical stimulation (200-300 mu A, 80 Hz, 30 s; n=4) caused a significant rise in brood pressure of 21+/-4 mmHg and 25+/-5 mmHg, respectively. These changes were associated with no overall effect on heart rate. The effects of electrical stimulation were found to be repeatable. 3 Pretreatment i.c.v. with pirenzepine (5-20 nmol; n=6-7 for each dose), dose-dependently inhibited the rise in blood pressure induced by carbachol, whereas AF-DX 116 (100 nmol; n=6) failed to have any effect on the carbachol-induced pressure response. Neither antagonist alone had any effect on resting baseline variables. 4 Unilateral microinjections of atropine sulphate (1-100 nmol; n=4-6 for each dose), pirenzepine (0.03-10 nmol; n=4 for each dose) or AF-DX 116 (10-60 nmol; n=4-5 for each dose), into the amygdala, dose-dependently inhibited the rise in blood pressure caused by electrical stimulation (200-300 mu A). The ID50 values were 1.05, 0.23 and 39.5 nmol, respectively. Although pirenzepine seemed to be more potent than atropine, this difference was not significant. 5 It is concluded that the rise in blood pressure elicited by unilateral microinjection of carbachol into,or electrical stimulation of, the amygdaloid complex is mediated by M-1-muscarinic receptors.
Keywords: muscarinic receptors; M-1-muscarinic receptors; carbachol; atropine; pirenzepine; AF-DX 116; amygdala; blood pressure; conscious rats; NUCLEUS TRACTUS SOLITARII; CHOLINERGIC MECHANISMS; CARDIOVASCULAR-RESPONSES; ANESTHETIZED CATS; BLOOD-PRESSURE; RECEPTORS; AREA; AGONISTS; CHOLINOMIMETICS; HYPERTENSION